Effect of Paprika on the ovarian development of africanized honeybee workers (Apis mellifera L.) in Queenless colonies - Carneiro, Giane Daniela [UNESP]; Chaud-Netto, José [UNESP]; Arruda, Valeska Marques [UNESP]; Brochetto-Braga, Márcia Regina [UNESP] (My University, 2008)
This paper deals with the influence of paprika in the ovarian development of Africanized honeybee workers in recently orphaned colonies. A beehive, whose queen had been naturally mated, was divided into two orphan nuclei. One was fed with candy once a week. The other nucleus received candy (47.5g) plus paprika (2.5g). Newly-emerged workers of both colonies were marked with paint and later collected and dissected at 15, 20, 25, 30, 35, 40 and 45 days of age, in order to compare the ovarian development. A considerable difference between the two groups of bees in relation to the frequency of workers with inactive and active ovaries was observed. A precocious ovarian development was detected in 15-day-old workers who received paprika. This result could be explained by the fact that paprika presents a great concentration of bixin, a carotene that is rich in vitamin A.
Keywords: Apis mellifera; Bixa orellana; Orphan workers; Ovarian development; Paprika